Intellectual Disability and Psychotropic Medications. Issue 7 (September 2018) - Herzig, Lisa; de Lacy, Nina; Capone, George; Radesky, Jenny
Abstract : CASE: Andrew is a 17-year-old male with trisomy 21, commonly known as Down syndrome, and accompanying severe intellectual disability who presents to your primary care office with his father for the first time to establish care and assistance with transition. Andrew has a history of a complete atrioventricular canal that was repaired as an infant and poorly controlled infantile spasms. Currently, he struggles with constipation, esophageal strictures, medullary nephrocalcinosis, urinary retention, sleep dysregulation, G-tube dependency, and hip dysplasia. Andrew walked at 11 to 12 years of age. Currently, he ambulates on his feet at home and in a wheelchair out in the community. He is nonverbal but can imprecisely sign for "more" and understands a few words. His father reports that his main concern is long-standing nonsuicidal self-injury (NSSI) and aggression. His self-injury consists of head banging against hard objects such as concrete floors and biting or scratching himself to the point of bleeding. Over the past 13 years, he has been prescribed over 10 different psychotropic medications, including various typical and atypical antipsychotics, selective serotonin reuptake inhibitors, benzodiazepines, mood stabilizers, and alpha agonists, all of which were discontinued because of the perception of undesirable side effects or lack of efficacy. His current medications include aripiprazole, olanzapine, levetiracetam, clorazepate, and trazodone. To rule out causes of irritability, you order a brain and spine magnetic resonance imaging, metabolic testing (for causes of NSSI such as Lesch-Nyhan), an autoimmune workup (for causes of pain or inflammation such as juvenile idiopathic arthritis), and hearing/vision testing, which are all normal. Previous testing by subspecialists (he is followed by gastroenterology, sleep medicine, orthopedics, nephrology, neurology, cardiology, and psychiatry) included normal renal ultrasound and no clear sources of gastrointestinal pain. However, key providers are spread among multiple institutions and do not regularly communicate. Andrew lives with his parents, who are highly educated and very dedicated to his health and wellness. His mother travels frequently for work, and his father is Andrew's full-time caregiver. Despite remaining ostensibly positive, his father reports significant caregiver burnout and fatigue. Over the next several months, Andrew continues to experience worsening NSSI necessitating medication changes despite active involvement in applied behavior analysis therapy. During this time, he presents to the emergency department multiple times for irritability and self-injury. On examination, he is aggressive, irritable, has bruises on his forehead and scratches on his skin, and has intermittent vertical gaze deviation that was noticeable to parents. The rest of his physical and neurological examination was unremarkable and revealed no asymmetry, clonus, hyperreflexia, or changes in muscle tone. While examining his extremities, joints, and abdomen, there was no obvious source of pain. What are your next steps? How would you support this family, both in the immediate management of his self-injury and long-term care needs for this medically and behaviorally complex adolescent?